Elaboration Of Sor Paradigm Using Information Transparency And Curiosity Variables Approach To Purchase Intention - Irantha Hendrika Kenang; Junko Alesandro; Alexander Marfin Sutanto Putra (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
This study uses S-O-R theory to determine the effect of Information Transparency and Curiosity on the Purchase Intention of the Comme business. This research is a quantitative research. Primary data is collected using questionnaires. The sampling technique uses purposive sampling with a total of 100 respondents. The results showed that Information Transparency has a significant effect on Curiosity and Curiosity has a significant effect on Purchase Intention. Based on the results of this study, the Comme business is expected to be able to consider the quality and quantity of information shared on Instagram which can affect consumer affection such as curiosity and thus increase consumer purchase interest